Feasibility Analysis Of The Provision Of Earthquake-Resistant Construction House (ERCH) Infrastructure With The Government And Business Entity Cooperation Scheme (GBECS) - Agung Barokah Waseso; Ayomi Dita Rarasati; Henki Wibowo Ashadi; Vian Marantha Haryanto (Green Publisher Indonesia, 2024)
Indonesia, situated on tectonic plate boundaries, is highly susceptible to earthquakes that cause significant damage to infrastructure and housing, particularly impacting low-income communities (LIC). This study evaluates the feasibility of providing Earthquake-Resistant Construction Houses (ERCH) through a Public-Private Partnership (PPP) scheme. Using qualitative and quantitative methods, the research examines technical, financial, and economic aspects of the PPP scheme, focusing on earthquake-resistant technologies and the involvement of government and business entities. Findings indicate that the PPP scheme effectively addresses challenges such as limited government budgets and land availability while promoting the construction of 10,000 special housing units for disaster-prone areas under Indonesia’s 2020–2024 Infrastructure Development Framework. Financial analysis shows a 25% Internal Rate of Return (IRR), a payback period of four years, and sustainable viability through private-sector participation and government guarantees. This study highlights the potential of PPP schemes to enhance disaster resilience, optimize resources, and provide sustainable housing solutions for vulnerable communities.